Suspicious minds : the dramatisation of paranoia in Victorian poetry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Frost, Sarah Lee (Massey University, 1999)
This thesis contains readings of a number of Victorian poems by Alfred Tennyson, Robert Browning and Dante Gabriel Rossetti which dramatise paranoia and jealousy. A range of twentieth-century theories of paranoia (including clinical, Freudian and Lacanian) have been used as explanatory tools for interpreting the representations of paranoia in the poems. The reading of Tennyson's Maud is based on Freud's theory of homoerotic motives. The reading of Browning's "'Childe Roland to the Dark Tower Came'" is based on the Lacanian concepts of foreclosure and the Name-of-the-Father. The readings of the jealousy poems are based on both theories, and this section includes a discussion of the limitations of the theories as explanatory tools. The general approach has been to apply clinical and psychoanalytical constructs and explanations to each poem separately, although there is some discussion involving the comparison of paranoid behaviours and motives across all the poems. Areas for further research are suggested in the concluding chapter.
Keywords: English poetry -- 19th century; History and criticism; Paranoia -- In literature